Effect of gamma rays on some electrical properties of high density polyethylene (HDPE) dissolved in tetrahydrofuran (THF) (Journal of the College of Basic Education, 2022)
This research includes a study of some electrical properties of high-density polyethylene dissolved in tetrahydrofuran before and after irradiation with gamma radiation and a radiation dose of (4000 rad) and a radiation rate of (181.8181 rad / min) for a period of (22 min).